Digital holographic microscopy for three-dimensional studies of bacteria - Flewellen, J (2012)
Holography has the ability to render three-dimensional information of a recorded scene by capturing both the amplitude and phase of light incident on the recording medium. The application of digital camera technology and high-speed computing means digital holograms can be analysed numerically and novel applications can be found for this technology. This thesis explores the potential for both inline and off-axis digital holographic microscopy to study the three-dimensional swimming behaviour of bacteria. A high-magnification (225x) digital holographic microscope was designed and constructed with the ability to switch easily between inline and off-axis imaging modalities. Hardware aspects, in particular the illumination source, the choice of camera and data transfer rates, were considered. Novel strategies for off-axis holography combining dark field microscopy were designed and implemented. The localisation accuracy of the inline imaging modality was assessed by studying samples of polystyrene microspheres. The microscope is sensitive to stage drift on the order of angstroms per second and can successfully localise microspheres in dilute suspensions at least 100μm from the objective specimen plane. As a simple test of the capabilities of the microscope, the diffusion coefficient of a 0.5μm microsphere was found to be isotropic and consistent with the theoretical value. Amplitude and phase image reconstructions from the off-axis modality are demonstrated. High-magnification dark field off-axis holographic microscopy is shown to be superior to inline microscopy in localising 100nm gold nanoparticles. An artifact from our method of dark-field imaging, however, restricts the depth range to 15μm. A lower-magnification (45x) configuration of the microscope was used to study the 3D swimming behaviour of wild type Escherichia coli as a qualitative demonstration of the potential for this instrument in microbiological applications.